2015
DOI: 10.1016/j.cortex.2015.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal white matter connections between medial frontal regions predict symptoms in patients with first episode schizophrenia

Abstract: Introduction The medial orbitofrontal cortex (mOFC) and rostral part of anterior cingulate cortex (rACC) have been suggested to be involved in the neural network of salience and emotional processing, and associated with specific clinical symptoms in schizophrenia. Considering the schizophrenia dysconnectivity hypothesis, the connectivity abnormalities between mOFC and rACC might be associated with clinical characteristics in first episode schizophrenia patients (FESZ). Methods After parcellating mOFC into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 91 publications
2
14
1
Order By: Relevance
“…Several studies found associations between delusions or hallucinations and WM microstructure in the arcuate fasciculus, cingulate bundle, corpus callosum, superior longitudinal fasciculus, inferior fronto-occipital fasciculus and the connection between the amygdala and the nucleus accumbens ( Bracht et al, 2014 , Hubl et al, 2004 , Seok et al, 2007 , Szeszko et al, 2008 ). In addition, recent studies found associations of hallucination and delusion severity with WM microstructure in the right inferior longitudinal fasciculus and the connection between the right posterior middle orbitofrontal cortex and the rostral part of the anterior cingulate cortex ( Ohtani et al, 2015 , Seitz et al, 2016 ). Only for delusions researchers found associations with WM properties in the cingulum bundle ( Whitford et al, 2015 ), fornix and external capsule ( Arnedo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies found associations between delusions or hallucinations and WM microstructure in the arcuate fasciculus, cingulate bundle, corpus callosum, superior longitudinal fasciculus, inferior fronto-occipital fasciculus and the connection between the amygdala and the nucleus accumbens ( Bracht et al, 2014 , Hubl et al, 2004 , Seok et al, 2007 , Szeszko et al, 2008 ). In addition, recent studies found associations of hallucination and delusion severity with WM microstructure in the right inferior longitudinal fasciculus and the connection between the right posterior middle orbitofrontal cortex and the rostral part of the anterior cingulate cortex ( Ohtani et al, 2015 , Seitz et al, 2016 ). Only for delusions researchers found associations with WM properties in the cingulum bundle ( Whitford et al, 2015 ), fornix and external capsule ( Arnedo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, WM microstructure in the splenium of the corpus callosum, the retrolenticular limb and posterior limb of the internal capsule have previously been associated with negative symptoms ( Arnedo et al, 2015 ). Additionally, fibertracking studies revealed correlations of negative symptoms with WM connections between the ventral tegmental area and the amygdala, the nucleus accumbens and the orbitofrontal cortex and between the anterior cingulate cortex and the orbitofrontal cortex ( Bracht et al, 2014 , Ohtani et al, 2014 , Ohtani et al, 2015 ). Contrary, there is one study of never-medicated first episode schizophrenia patients, which found no correlations between FA and negative symptoms ( Cheung et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more, anatomical changes of these structures are related to mental disorders. For instance, schizophrenic patients showed reduced levels of gray matter volume in anterior cingulate cortex (ACC; Yamasue et al, 2004 ) and the connectivity of this structure with other brain regions could also play a role in first-episode schizophrenia development (Ohtani et al, 2015 ) and might be related to negative symptoms in schizophrenia (Ohtani et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…These receptors might have an excitotoxic effect on neurons, becoming a target for therapeutic agents [ 30 ]. Magnetic resonance imaging has revealed many disturbances in the function and density of glial cells, particularly the oligodendrocytes forming myelin, in the prefrontal WM of patients with schizophrenia [ 31 , 32 , 33 , 34 ]: decreased regional and global WM volumes [ 35 , 36 , 37 , 38 ], decreased ratios of magnetization transfer [ 39 , 40 ] and anisotropy of diffusion tensor imaging [ 41 , 42 , 43 , 44 , 45 ], all of which may indicate a possible pathology of myelin and WM in general [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%